Spirituality and nature connectedness as mediators between exposure to nature and psychological well-being of school students - Md Sahak, Siti Nabihah; Roslan, Samsilah; Ahmad, Noorlila; Zaremohzzabieh, Zeinab; Mohamad, Zulkifli; Ma’rof, Aini Marina (Asia Pacific Academy of Science Pte Ltd, 2024)
Spiritual meditations practiced within green environments develop a perceived interconnection between the self and nature that influences physiological well-being. This study investigates spirituality and natural connectivity as mediators between exposure to nature and psychological well-being in Malaysian school students. This study involved 293 students (178 female and 115 male) from four secondary schools in the Johor Bahru district with survey findings on the Exposure to Nature Scale, Connectedness to Nature Scale, Spiritual Values Scale, and Psychological Well-being Scale. The students in the study fell within the age range of 13 to 16 years, and the average age of the sample was 11.86 ± 2.32 years. Structural equation modeling indicated that high spirituality and nature connectedness mediated the relationship between exposure to nature and psychological well-being. Spirituality significantly influenced the relationship between exposure to nature and psychological well-being more than nature connectedness. These findings indicate that practitioners appreciate the value of certain aspects, like exposure to nature, nature connectedness, and spirituality, as a possible path for enhancing school students’ psychological well-being.